PHENOLIC AND FLAVONOID CONTENT AND ANTIOXIDANT EVALUATION OF HAWTHORN (Crataegus monogyna Jacq.) FRUITS AND LEAVES EXTRACTS - Dekić, Vidoslav; Ristić, Novica; Dekić, Biljana; Ristić, Milenko (Bulletin of Natural Sciences Research, 2020)
Considering the facts that phenolic compounds have many pharmacological effects, as well that antioxidant effect of phenolic compounds has been proven in various experimental systems, aim of this research was to determine the content of total phenols and flavonoids and evaluation of antioxidant activity in ethanol, ethyl acetate and chloroform extracts of fruits and leaves of the plant species Crataegus monogya Jacq., which is known as common hawthorn. The content of total phenolic compounds was determined by the spectrophotometric method using Folin-Ciocalteu reagent and the content of flavonoids was determined using aluminum chloride. In vitro evaluation of the antioxidant activity of tested extracts was performed using the DPPH method. The amount of total phenolics was varied in fruits and leaves extracts and ranged from 38.05 ± 0.18 to 365.11 ± 0.32 mg GAE/g dw. Ethyl acetate extract of hawthorn leaves showed the highest content of phenolic compounds (365.11 ± 0.32 mg GAE/g dw). The flavonoid content was different in the fruits and leaves of hawthorn and ranged from 21.11 ± 0.11 to 122.98 ± 0.21 mg RU/g dw, whereby the highest content of flavonoids was found in ethyl acetate extract of leaves (122.98 ± 0.21 mg RU/g dw). Antioxidant activity of the tested extracts was expressed as IC50 values and ranged from 5.53 ± 0.08 to 293.51 ± 0.28 μg/ml. Ethyl acetate extract of hawthorn leaves showed considerable antioxidant potential (IC50 = 5.53 ± 0.08 μg/ml). Based on the obtained results, a significant correlation was found between the antioxidant activity and the content of total phenolics and flavonoids compounds in hawthorn fruits and leaves extracts.